Fuel Wood Production in India - an Evaluation - Trivedi, S. N. (Indian Forester, 1986)
India is the biggest fuelwood producing country in the world. This article is an atempt to study the trend of production of fuelwood and other energy commodities in India over the years and tha role of the fuelwood in the rural energy budget as compared to some other countries. The articles throws light on the alarming situation of the fuelwood deficit, its effect on deforestation and emphasizes the need to chalk out a mere dynasis and extensive programme of fuelwood plantations.